2014
DOI: 10.5535/arm.2014.38.1.122
|View full text |Cite
|
Sign up to set email alerts
|

Videofluoroscopy-Guided Balloon Dilatation for the Opening Dysfunction of Upper Esophageal Sphincter by Postoperative Vagus Nerve Injury: A Report on Two Cases

Abstract: Dysphagia secondary to peripheral cranial nerve injury originates from weak and uncoordinated contraction-relaxation of cricopharyngeal muscle. We report on two patients who suffered vagus nerve injury during surgery and showed sudden dysphagia by opening dysfunction of upper esophageal sphincter (UES). Videofluoroscopy-guided balloon dilatation of UES was performed. We confirmed an early improvement of the opening dysfunctions of UES, although other neurologic symptoms persisted. While we did not have a prope… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 7 publications
0
2
0
Order By: Relevance
“…This method incorporated the idea of dilatation, but instead of keeping the balloon in the expanded state at the UES for some time, it mainly utilized iterative swallowing responses, which could be spontaneous, voluntary, or reflexive by irritation of the nerve plexus by the expanded balloon. Recently, Jung et al [ 14 ] reported cases of two patients, who were able to take oral feeding after application of technique suggested by Kim et al [ 13 ] in patients with UES dysfunction due to vagus nerve injury after a surgical intervention.…”
Section: Introductionmentioning
confidence: 99%
“…This method incorporated the idea of dilatation, but instead of keeping the balloon in the expanded state at the UES for some time, it mainly utilized iterative swallowing responses, which could be spontaneous, voluntary, or reflexive by irritation of the nerve plexus by the expanded balloon. Recently, Jung et al [ 14 ] reported cases of two patients, who were able to take oral feeding after application of technique suggested by Kim et al [ 13 ] in patients with UES dysfunction due to vagus nerve injury after a surgical intervention.…”
Section: Introductionmentioning
confidence: 99%
“…[ 21 23 ] In other ways, there are some reports of cricopharyngeal balloon dilatation using urethral catheters under fluoroscopic guidance, showing pharyngoesophageal function improvements. [ 24 26 ] In a study that used high-resolution manometry, balloon dilatation using urethral catheters for CPD improved UES relaxation, restored UES resting pressure, strengthened pharyngeal propulsion, and improved functional oral intake, compared with regular therapy alone. [ 27 ] Alternatively, RBS is a safer approach than mechanical balloon dilatation of the UES.…”
Section: Discussionmentioning
confidence: 99%